Calcium intake and risk of primary hyperparathyroidism in women: prospective cohort study. (18th October 2012) - Paik, Julie M; Curhan, Gary C; Taylor, Eric N
Abstract : Objective To examine the association between calcium intake and risk of primary hyperparathyroidism in women. Design Prospective cohort study. Setting Nurses' Health Study I, which originally recruited participants from the 11 most populous states in the United States. Participants 58 354 female registered nurses enrolled in the Nurses' Health Study I aged 39-66 years in 1986 and with no history of primary hyperparathyroidism. Calcium intake was assessed every four years using semiquantitative questionnaires on food frequency. Main outcome measure Incident primary hyperparathyroidism, confirmed by medical record review. Results During 22 years of follow-up, we recorded 277 incident cases of primary hyperparathyroidism. Women were divided into five equal groups, according to intake of dietary calcium. After adjusting for age, body mass index, race, and other factors, the relative risk of primary hyperparathyroidism for women in the group with the highest intake of dietary calcium was 0.56 (95% confidence interval 0.37 to 0.86, P=0.009 for trend), compared with the group with the lowest intake. The multivariable relative risk of primary hyperparathyroidism for women taking more than 500 mg/day of calcium supplements compared with no calcium supplements was 0.41 (95% confidence interval 0.29 to 0.60, P<0.001 for trend). Analyses restricted to participants with regular physical exams did not significantly change the association between calcium intake and risk of primary hyperparathyroidism. Conclusion Increased calcium intake is independently associated with a reduced risk of primary hyperparathyroidism in women.